Genome-wide scans for signatures of selection in Mangalarga Marchador horses using high-throughput SNP genotyping - Santos, Wellington B. [UNESP]; Schettini, Gustavo P. [UNESP]; Maiorano, Amanda M. [UNESP]; Bussiman, Fernando O.; Balieiro, Júlio C. C.; Ferraz, Guilherme C. [UNESP]; Pereira, Guilherme L. [UNESP]; Baldassini, Welder Angelo [UNESP]; Neto, Otávio R. M. [UNESP]; Oliveira, Henrique N. [UNESP]; Curi, Rogério A. [UNESP] (Springer Nature, 2021)
Background: The detection of signatures of selection in genomic regions provides insights into the evolutionary process, enabling discoveries regarding complex phenotypic traits. In this research, we focused on identifying genomic regions affected by different selection pressures, mainly highlighting the recent positive selection, as well as understanding the candidate genes and functional pathways associated with the signatures of selection in the Mangalarga Marchador genome. Besides, we seek to direct the discussion about genes and traits of importance in this breed, especially traits related to the type and quality of gait, temperament, conformation, and locomotor system. Results: Three different methods were used to search for signals of selection: Tajima’s D (TD), the integrated haplotype score (iHS), and runs of homozygosity (ROH). The samples were composed of males (n = 62) and females (n = 130) that were initially chosen considering well-defined phenotypes for gait: picada (n = 86) and batida (n = 106). All horses were genotyped using a 670 k Axiom® Equine Genotyping Array​ (Axiom MNEC670). In total, 27, 104 (chosen), and 38 candidate genes were observed within the signatures of selection identified in TD, iHS, and ROH analyses, respectively. The genes are acting in essential biological processes. The enrichment analysis highlighted the following functions: anterior/posterior pattern for the set of genes (GLI3, HOXC9, HOXC6, HOXC5, HOXC4, HOXC13, HOXC11, and HOXC10); limb morphogenesis, skeletal system, proximal/distal pattern formation, JUN kinase activity (CCL19 and MAP3K6); and muscle stretch response (MAPK14). Other candidate genes were associated with energy metabolism, bronchodilator response, NADH regeneration, reproduction, keratinization, and the immunological system. Conclusions: Our findings revealed evidence of signatures of selection in the MM breed that encompass genes acting on athletic performance, limb development, and energy to muscle activity, with the particular involvement of the HOX family genes. The genome of MM is marked by recent positive selection. However, Tajima’s D and iHS results point also to the presence of balancing selection in specific regions of the genome.
Keywords: DMRT3; Equine genotyping array; Gaited horse breeds; iHS; ROH; Tajima’s D